A molecular dynamics simulation investigation of the relative stability of the cyclic peptide octreotide and its deprotonated and its (CF3)-Trp substituted analogs in different solvents - Smith, L; Rought Whitta, G; Dolenc, J; Wang, D; van Gunsteren, W (Elsevier, 2016)
The cyclic octa-peptide octreotide and its derivatives are used as diagnostics and therapeutics in relation to particular types of cancers. This led to investigations of their conformational properties using spectroscopic, NMR and CD, methods. A CF3-substituted derivative, that was designed to stabilize the dominant octreotide conformer responsible for receptor binding, turned out to have a lower affinity. The obtained spectroscopic data were interpreted as to show an increased flexibility of the CF3 derivative compared to the unsubstituted octreotide, which could then explain the lower affinity. In this article, we use MD simulation without and with time-averaged NOE distance and time-averaged local-elevation 3J-coupling restraining representing experimental NMR data to determine the conformational properties of the different peptides in the different solvents for which experimental data are available, that are compatible with the NOE atom-atom distance bounds and the 3JHNHα-couplings as derived from the NMR measurements. The conformational ensembles show that the CF3 substitution in combination with the change of solvent from water to methanol leads to a decrease in flexibility and a shift in the populations of the dominant conformers that are compatible with the experimental data.